MASALAH PEREMPUAN DALAM PERBINCANGAN ISLAM DAN KONFLIK PERAN: Perempuan, Islam, Problem Perempuan, Peran ganda - SALMA, SALMAWATI RUMADAN (Jurnal Studi Islam, 2025)
The issue of gender in an Islamic perspective lies on a priority scale where elements of awareness of women's liberation are based on the Islamic struggle. Based on these things, the researcher will explore several problems including: 1) How does Islam view gender? ; 2) What are the views of Muslim female figures regarding gender and what are the dual roles that women face as mothers and career women? ; 3) What about role conflict for women? . In this case the author carried out a library research method, namely research that collects data by collecting data from various literature, including books, documentary materials, magazines, journals and newspapers. The results of this research are first, gender is a society's views or beliefs about how a woman or a man should act or think. In Islam, as in the Holy Qur'an, it is explained that one of the principles of Islamic teachings (the Qur'an) is the teaching about equality between humans. Second, the views of several figures, including Musda Mulya, Nawal El Saadawi, Bint Syathi, provide different views but have a common core, namely that discrimination against women should be eliminated. Third, regarding role conflicts in women, where women often occur, especially for married women, it is not easy to position their role as either a career woman or a housewife, which then results in conflict between the two roles. Keywords; Women, Islam, Women's Problems Persoalan tentang gender dalam perspektif Islam terletak pada skala prioritas dimana unsur-unsur kesadaran pembebasan kaum perempuan yangberdasarkan perjuangan Islam. Permasalahan penelitian ini, yaitu 1) Bagaimana Islam memandang gender; 2) Bagaimaan pandangan tokoh perempuan muslim tentang gender dan peran ganda yang dihadapi perempuan? 3 ) Bagaimana konflik peran pada perempuan ? Jenis Penelitian ini merupakan penelitian pustaka yakni penelitian kualitatif yang pengumpulan datanya dari berbagai literatur, seperti dari buku-buku, bahan-bahan dokumen, majalah, jurnal, dan surat kabar. Hasil dari penelitian ini pertama, gender adalah pandangan atau keyakinan yang dibentuk oleh masyarakat tentang bagaimana seharusnya seseorang perempuan atau laki-laki bertingkah laku maupun berpikir. Dalam Islam sebagaimana dalam kitab Suci Al-Qur’an menerangkan salah satu prinsip dari ajaran Islam (Al-Qur’an) adalah ajaran tentang persamaan di antara manusia. Kedua, dari beberapa pandangan tokoh perempuan muslim di antaranya Musda Mulya, Nawal El Saadawi, Bint Syathi memberikan pandangan yang berbeda namun memiliki inti persamaan bahwa diskriminasi terhadap perempuan seharunya dihilangkan. Ketiga, mengenai konflik peran pada perempuan seringkali terjadi bagi wanita yang sudah menikah Ia tidak mudah untuk memposisikan peran baik sebagai wanita karir atau sebagai ibu rumah tangga yang kemudian terjadinya pertentangan antara dua peran tersebut. Kata Kunci ; Perempuan, Islam, Problem Perempuan